Adaptation Strategies of Migrant Students in Adjusting to a New Campus Environment - Encup Supriatna (STAI Hubbulwathan Duri, 2023)
This study aimed to explore the adaptation strategies used by migrant students to adjust to a new university environment. Using a qualitative approach, the study was conducted at a state Islamic university in Bandung, Indonesia. Data were collected through in-depth interviews with 20 migrant students from various regions in Indonesia. The findings of the study revealed several strategies used by migrant students, including seeking social support, participating in extracurricular activities, establishing a new routine, and managing finances. These strategies were effective in helping the migrant students to overcome the challenges of adjusting to a new campus environment. The study contributes to the literature on student migration and provides insights for universities to support the adaptation of migrant students better.